Histologic characterization of paediatric mesenchymal neoplasms treated with kinase‐targeted therapy. Issue 2 (29th May 2022) - Baranov, Esther; Winsnes, Katrina; O'Brien, Matthew; Voss, Stephan D; Church, Alanna J; Janeway, Katherine A; DuBois, Steven G; Davis, Jessica L; Al‐Ibraheemi, Alyaa
Abstract : Aims: Recurrent alterations involving receptor tyrosine or cytoplasmic kinase genes have been described in soft‐tissue neoplasms such as infantile fibrosarcoma (IFS) and inflammatory myofibroblastic tumour (IMT). Recent trials and regulatory approvals for targeted inhibitors against the kinase domains of these oncoproteins have allowed for increased use of targeted therapies. We aimed to characterize the histologic features of paediatric mesenchymal neoplasms with kinase alterations treated with targeted inhibitors. Methods and results: Eight patients with tyrosine kinase‐altered mesenchymal neoplasms with pre‐ and posttreatment samples were identified. Tumours occurred in five females and three males with a median age at presentation of 6.5 years. Tumour sites were bone/somatic soft‐tissue ( n = 5) and viscera ( n = 3). Pretreatment diagnoses were: IMT ( n = 3), epithelioid inflammatory myofibroblastic sarcoma ( n = 1), and descriptive diagnoses ( n = 4) such as "kinase‐driven spindle cell tumor." Fusions identified were ETV6::NTRK3 ( n = 2), TPM3::NTRK1, SEPT7::BRAF, TFG::ROS1, KLC1::ALK, RANBP2::ALK, and MAP4::RAF1 . Patients were treated with larotrectinib ( n = 3), ALK or ALK/ROS1 inhibitors ( n = 3), and MEK inhibitors ( n = 2). Posttreatment tumours exhibited a striking decrease in cellularity (7/8) and the presence of collagenous stroma (7/8) with extensive glassy hyalinization (5/8). In two cases, abundant coarse or psammomatous calcifications were seen and in one case prominent perivascular hyalinization was noted. Residual viable tumour was seen in 3/8 cases (<5% in one case, and >75% in 2/8 cases). Conclusion: Mesenchymal neoplasms with tyrosine kinase alterations treated with targeted inhibitors show a pathologic response, which includes decreased cellularity and stromal hyalinization. The presence of these features may be helpful in assessing tumour response after targeted therapy. Abstract :